2017
DOI: 10.1161/circulationaha.117.028087
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Adenosine on Atrioventricular Nodal Conduction in Pediatric and Young Adult Patients After Heart Transplantation

Abstract: Background Supraventricular tachycardia (SVT) is common after heart transplant. Adenosine, the standard therapy for treating SVT in children and adults without transplant, is relatively contraindicated post-transplant due to a presumed risk of prolonged atrioventricular (AV) block in denervated hearts. This study tested whether adenosine caused prolonged asystole after transplant and if it was effective in blocking AV nodal conduction in these patients. Methods This was a single center prospective clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
0
22
0
2
Order By: Relevance
“…In addition to promising preclinical research to decipher the complex role of nucleotide signaling in solid organ transplantation, several clinical trials are ongoing or have concluded that address purinergic signaling in the context of transplantation (see Table ). To date, only one study (NCT02462941) has been published whereby Flyer et al showed that adenosine induces atrioventricular block in healthy pediatric and young adult heart transplant recipients with minimal risk when low initial doses are used . Another study (NCT03231371) is currently evaluating the potential protective role of adenosine treatment in vasculopathy in heart transplantation, and another ongoing study (NCT03072589) is evaluating the maximum safe dose and duration of regadenoson (an A2AR agonist) in lung transplant patients as a means to prevent primary graft dysfunction.…”
Section: Purinergic Signaling As a Target For Improving Transplant Oumentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to promising preclinical research to decipher the complex role of nucleotide signaling in solid organ transplantation, several clinical trials are ongoing or have concluded that address purinergic signaling in the context of transplantation (see Table ). To date, only one study (NCT02462941) has been published whereby Flyer et al showed that adenosine induces atrioventricular block in healthy pediatric and young adult heart transplant recipients with minimal risk when low initial doses are used . Another study (NCT03231371) is currently evaluating the potential protective role of adenosine treatment in vasculopathy in heart transplantation, and another ongoing study (NCT03072589) is evaluating the maximum safe dose and duration of regadenoson (an A2AR agonist) in lung transplant patients as a means to prevent primary graft dysfunction.…”
Section: Purinergic Signaling As a Target For Improving Transplant Oumentioning
confidence: 99%
“…Flyer et al showed that adenosine induces atrioventricular block in healthy pediatric and young adult heart transplant recipients with minimal risk when low initial doses are used. 64 Another study The authors also acknowledge the many excellent papers in the field that, due to space constraints, could not be directly referenced in the current review.…”
Section: Purinerg I C S I G Naling a S A Targ E T For Improving Tr mentioning
confidence: 99%
“…However, a recent case series of patients in sinus rhythm following cardiac transplant given adenosine showed no major adverse events, including asystole, or need for pacing, which calls these views into question. [ 167 ]…”
Section: Adverse Effects and Contraindications Of Adenosinementioning
confidence: 99%
“…Moreover, the NOMO1 gene has also been identified that it is evidently down-regulated in human ventricular septal defect myocardium, and it was found that knockdown of NOMO1 gene inhibited the differentiation of P19 cells into cardiomyocytes [17]. Nodal is a member of transforming growth factor-b (TGF-b), which acts as an essential role on heart development and formation of other visceral organs [18]. Nodal is also important for the maintenance of pluripotency of embryonic stem cells and germ layer specification [19].…”
Section: Introductionmentioning
confidence: 99%